Returning too soon? Australian Mothers' Satisfaction with maternity leave duration - Hosking, A; Whitehouse, Gillian; Baird, Marian (My University, 2008)
This paper examines the question of optimal duration of maternity leave through the lens of Australian mothers' perceptions of satisfaction with their leave: specifically, whether and why they returned to work earlier than they would have liked. Analysis of The Parental Leave in Australia Survey identifies financial need and limited access to paid maternity leave as the most common reasons for returning `early'. Mothers taking leave for less than 9 months were significantly more likely than those taking longer periods to report that they had returned earlier than they wanted to, although leave periods over 12 months were not consistently associated with further declines in dissatisfaction with duration. Overall, the analysis highlights the financial pressures underpinning women's decisions, and suggests that enhanced availability of paid leave is more likely to be welcomed than further extension of leave duration.
Asia Pacific Journal of Human Resources
Keywords: Families; Employment -- Conditions; Employment; Families -- Mothers; Families and relationships; Labour market; Families; Employment; Conditions; Mothers; Families and relationships; Employment and unemployment